2005
DOI: 10.1186/1471-2474-6-33
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density measurement and osteoporosis treatment after a fragility fracture in older adults: regional variation and determinants of use in Quebec

Abstract: Background: Osteoporosis (OP) is a skeletal disorder characterized by reduced bone strength and predisposition to increased risk of fracture, with consequent increased risk of morbidity and mortality. It is therefore an important public health problem. International and Canadian associations have issued clinical guidelines for the diagnosis and treatment of OP. In this study, we identified potential predictors of bone mineral density (BMD) testing and OP treatment, which include place of residence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 30 publications
(28 reference statements)
3
25
0
1
Order By: Relevance
“…Encouragingly, post hoc analyses have demonstrated the efficacy of several anti-fracture therapies in preventing fragility fractures in osteopenic women [38][39][40]. Similar to the findings of this investigation, a retrospective database study previously completed in Quebec reported that, after a fragility fracture, significant predictors of osteoporosis treatment included age, social status and prior DXA BMD testing [41]. However, different from the findings reported in this study, the probability of antifracture treatment decreased with increasing age after 75 years of age, with no difference in treatment rates between those aged 65-69 and 70-74 years.…”
Section: Discussionsupporting
confidence: 72%
“…Encouragingly, post hoc analyses have demonstrated the efficacy of several anti-fracture therapies in preventing fragility fractures in osteopenic women [38][39][40]. Similar to the findings of this investigation, a retrospective database study previously completed in Quebec reported that, after a fragility fracture, significant predictors of osteoporosis treatment included age, social status and prior DXA BMD testing [41]. However, different from the findings reported in this study, the probability of antifracture treatment decreased with increasing age after 75 years of age, with no difference in treatment rates between those aged 65-69 and 70-74 years.…”
Section: Discussionsupporting
confidence: 72%
“…Studies have shown chronic glucocorticoid use and prior history of fracture to be predictors for DEXA testing in the general population, similar to our study. [28][29][30][31] Age !55 years has been shown to increase DEXA use in at-risk individuals in the general population; however, the very elderly (age !75 years) had decreased use in these studies. 30,31 While our study was in a predominantly male population, others have found at-risk men in the general population undergo less testing than women.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31] Age !55 years has been shown to increase DEXA use in at-risk individuals in the general population; however, the very elderly (age !75 years) had decreased use in these studies. 30,31 While our study was in a predominantly male population, others have found at-risk men in the general population undergo less testing than women. 28,30 The only negative predictor for DEXA testing in our study was a history of an IBD-related hospital admission.…”
Section: Discussionmentioning
confidence: 99%
“…However, it failed to remain important throughout the variable selection procedures in both sets of multivariable models. A likely explanation for this phenomenon is that many of the characteristics that predict fracture in our models, such as having a prior fracture, being very elderly, and being underweight, are the same characteristics that cue clinicians to order a BMD test [16]. Thus, BMD orders became nonsignificant when adjusted for those other characteristics.…”
Section: Incidence Of Fracturementioning
confidence: 61%